Perancangan Motion Comic Cerita Pewayangan Bima dan Dewa Ruci untuk Masalah Krisis Identitas pada Remaja - Ardiyansyah, Riyan; Kurniawan, Rahmat; Poerbaningtyas, Evy (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
Adolescent identity crisis poses risks of leading youths toward negative behaviors such as depression, delinquency, and substance abuse. This design initiative aims to develop a motion comic as an educational tool for teenagers to navigate their self-identity. Employing Design Thinking, the process involves qualitative methods including 5W+1H analysis, interviews, literature review, document analysis, and online research. The motion comic, "Bima and Dewa Ruci," underwent alpha and beta testing for addressing adolescent identity crisis. Findings suggest that while the motion comic can aid learning, it falls short in inducing significant psychological and character changes. Further refinement is necessary for optimal effectiveness. This study emphasizes the potential of motion comics as supplementary educational resources in understanding and addressing adolescent identity crises.